The role of annealing ambient on diffusion of implanted Si in β-Ga2O3 - Ribhu Sharma; Mark E. Law; Chaker Fares; Marko Tadjer; Fan Ren; A. Kuramata; S. J. Pearton (AIP Advances, 2019)
The most common n-type dopant, Si, was implanted into bulk (-201) β-Ga2O3 at total doses from 2x1013-2x1015 cm-2 and annealed at 1100 °C for 10-120 secs in either O2 or N2 ambients. Secondary Ion Mass Spectrometry profiling showed a significant effect of the annealing ambient on the Si diffusivity. In the case of O2 annealing, there was extensive redistribution of the Si across the entire dose range, while in sharp contrast, the use of N2 annealing suppressed the Si diffusion. The results are consistent with a defect-assisted process. Excellent fits to the Si profiles were obtained with the FLOOPS simulator, assuming mobile vacancy/defect concentrations as the important factor for the difference in the O2 vs N2 annealing ambients. One possibility is that for N2 anneals, more Ga vacancies are created, enabling interstitial Si to migrate onto a substitutional Ga site where it has low diffusivity. The N2 ambient also suppresses loss of Si to the surface, with >90% of the initial dose retained after annealing at 1100 °C for 120 secs, compared to 66-77% with O2 anneals under the same conditions.